The Relationship Of Narcism Behavior In Tiktok Applications With Adolescent Personality (Study In High School Students (SMA) Negeri 2 Central Bengkulu) - Irawan, Dodi; Asnawati, Asnawati; Indasari, Fera (SENGKUNI Journal (Social Science and Humanities Studies), 2021)
This study aims to determine the relationship between narcissistic behavior on the Tiktok application and the personality of teenagers in high school students (SMA) Negeri 2 Central Bengkulu. This shows that there is a strong and positive correlation between narcissistic behavior on the Tiktok application and the personality of adolescents at SMA Negeri 2 Bengkulu Tengah. This means that the higher the Narcissism Behavior on the Tiktok Application, the more it will reflect the personality of teenagers at the State 2 Central Bengkulu High School (SMA). From the results of hypothesis testing, the tcount value is 9.21 and then compared with the ttable value with the level of significance set at 95% with a one-way calculation and dk = n-2 = 40-2 = 38, it is known that the ttable value is 1.686. This explains that there is a close relationship between narcissistic behavior in the Tiktok application and adolescent personality in high school students (SMA) Negeri 2 Central Bengkulu.